2021
DOI: 10.1001/jamanetworkopen.2021.26719
|View full text |Cite
|
Sign up to set email alerts
|

Association of Public Reporting of Medicare Dialysis Facility Quality Ratings With Access to Kidney Transplantation

Abstract: IMPORTANCE Improving the quality of dialysis care and access to kidney transplantation for patients with end-stage kidney disease is a national clinical and policy priority. The role of dialysis facility quality in increasing access to kidney transplantation is not known. OBJECTIVETo determine whether patient, facility, and kidney transplant waitlisting characteristics are associated with variations in dialysis center quality. DESIGN, SETTING, AND PARTICIPANTS This population-based cohort study is an analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Referral data are not available in the USRDS. Nevertheless, 1-year incidence of wait-listing is a useful proxy for early referral and a metric of access to transplantation . Although this study focuses on dialysis facilities, the transplant centers play an undeniable role in ensuring access, and the impact of insurance and payer mix among transplant centers warrants exploration in future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Referral data are not available in the USRDS. Nevertheless, 1-year incidence of wait-listing is a useful proxy for early referral and a metric of access to transplantation . Although this study focuses on dialysis facilities, the transplant centers play an undeniable role in ensuring access, and the impact of insurance and payer mix among transplant centers warrants exploration in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Our primary outcome was time until addition to the kidney transplant waiting list up to 1 year after dialysis initiation (patient-level). This outcome was chosen in line with existing federal policy priorities and quality measures . We censored for death within 1 year of listing.…”
Section: Methodsmentioning
confidence: 99%
“…Given the relatively recent advent of transplantation in this patient population, it is perhaps possible that increasing provider knowledge about transplantation among PWH, could yield higher referral and waitlisting rates. Numerous studies have demonstrated that facility-level characteristics such as Medicare dialysis facility quality rating, ownership status, and center philosophy impact likelihood of waitlist addition and thus, these characteristics may explain some of the remaining unexplained disparity [40][41][42]. Nationally, Medicaid expansion has been associated with increased waitlist addition rates and improved survival on dialysis [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…While this is not the only reason that patients may switch early, any increase in switching could increase the substantial cost that Medicare already bears from the nearly one third of patients who switch early. 2 Because Medicare as a primary insurer at dialysis initiation is associated with decreased waitlisting for kidney transplantation, 35 early switching to Medicare may also be associated with decreased waitlisting for transplantation. Given the uncertainty around the net effect of Marietta on waitlisting, we used a 10-year pre- Marietta cohort to ( 1 ) assess the frequency and characteristics of patients who switched early to Medicare and ( 2 ) estimate the association of early switching to Medicare with waitlisting for kidney transplantation.…”
mentioning
confidence: 99%